Kontribusi Prodi Pendidikan dan Pengajaran Agama Katolik STAKat Negeri Pontianak dengan Dunia Kerja - Herkulanus Pongkot; Martinus Martinus; Mukarramah Mukarramah (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
This is a study of the situation of alumni, especially in terms of job search, work situations and the use of competency acquisition during college. The purpose of this activity is to collect relevant information and input from graduates related to the "learning and working experience" experienced by graduates for the development of higher education. The Tracer Study was carried out using a survey by method questionnaire, with the aim of obtaining information from STAKat Negeri Pontianak alumni in all regions in West Kalimantan. The results of the questionnaire can represent the overall results of this tracer study. The result were: First, the alumni of PPAK Study Program have decent jobs and most of them work as Catholic Religious Educators at various levels of primary to secondary education. Second, the competencies that alumni get while studying at the STAKat Negeri Pontianak are very relevant to their current world of work. Third, there are several gaps that occur, the first is; lack of English competence, the solution to this gap is by holding an English Day, English courses in the campus environment, updating more contextual teaching methods by lecturers and holding TOEFL as a condition for student graduation. The second, lack ability to work under pressure, solutions to this gap are spiritual mentors, use of problem solving based teaching methods and dynamic curriculum monitoring. The third gap is ability to write reports, memos and documents is not very good, the solution to this gap is by updating the curriculum that supports alumni's abilities when they enter the world of work, especially in the world of education.